Reconstruction of Certainty and Efficiency-Based Execution of Guarantee Objects: A Legal Comparative Approach - Basyarudin Basyarudin; Sahrul Hanafi (Rechtsvinding, 2026)
The execution of the object of collateral is a crucial phase in the material guarantee legal system because it determines the effectiveness of creditor protection and legal certainty in settling receivables. In Indonesian law, the Right of Dependency is designed as a guarantee instrument that gives preferential position and executory power to creditors. However, practice shows that the mechanism for the execution of the collateral object has not been fully implemented definitively and efficiently, and often even gives rise to further disputes. This study aims to analyze the structural problems of the execution of collateral objects in Indonesia and formulate a reconstruction of the execution mechanism based on legal certainty and efficiency through a comparative legal approach. This research uses normative legal research methods with legislative, conceptual, case, and comparative legal approaches. The results of the study show that the uncertainty of execution is caused by conflicts between legal regimes, ambiguity of execution norms, weak protection in execution auctions, and pre-execution problems related to the binding of guarantees. Through comparison with practices in other countries, this study found that the certainty and efficiency of execution can only be realized through coherent system design, post-execution dispute resolution, and harmonization between legal regimes. This research offers a reconstruction model of the execution of the collateral object that affirms the final character of the execution, strengthens the protection of parties in good faith, and integrates the principles of legal certainty and efficiency as a normative framework. This reconstruction is expected to be a reference for the renewal of the law on the execution of material guarantees in Indonesia